1995
DOI: 10.1016/1044-0305(95)00582-x
|View full text |Cite
|
Sign up to set email alerts
|

Mass and charge state assignment for proteins and peptide mixtures via noncovalent adduction in electrospray mass spectrometry

Abstract: A method has been developed that takes advantage of the formation of noncovalent compounds in electrospray mass spectrometry. Mixtures of proteins and peptides are shown to produce an intense ion that corresponds to a 1:1 complex with a crown ether (18-crown-6). Although the crown ether may be added directly to the solution, for the current experiments it is introduced via the methanol liquid sheath. The spacing of these complexed species in the mass spectrum allows unambiguous determination of the charge stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…In cases where sufficient resolution to assign the charge state from the isotopic pattern is not available, such as often happens with linear quadrupole analysers, the correct assignment can be made by measuring the distance between the signal and known adducts with some components of the mobile phase, either occurring incidentally such as sodium and/or potassium ions, or added on purpose such as crown ethers. 51 In the present case, the correct assignment to the monomer is possible by looking at the sodium adducts of m/z 1214 (di †ering from the deprotonated ion by 22/3 u) and m/z 1822 (di †ering by 22/2 u). Incidentally, the term "adductÏ does not appear to be strictly correct to describe such ions, since e †ectively here a sodium ion has replaced one mobile hydrogen in the molecule, and is not simply added to it ; however, it is generally accepted in similar cases, and hence it will be used also in this paper.…”
Section: Observation Of Duplex Oligodeoxynucleotidesmentioning
confidence: 98%
“…In cases where sufficient resolution to assign the charge state from the isotopic pattern is not available, such as often happens with linear quadrupole analysers, the correct assignment can be made by measuring the distance between the signal and known adducts with some components of the mobile phase, either occurring incidentally such as sodium and/or potassium ions, or added on purpose such as crown ethers. 51 In the present case, the correct assignment to the monomer is possible by looking at the sodium adducts of m/z 1214 (di †ering from the deprotonated ion by 22/3 u) and m/z 1822 (di †ering by 22/2 u). Incidentally, the term "adductÏ does not appear to be strictly correct to describe such ions, since e †ectively here a sodium ion has replaced one mobile hydrogen in the molecule, and is not simply added to it ; however, it is generally accepted in similar cases, and hence it will be used also in this paper.…”
Section: Observation Of Duplex Oligodeoxynucleotidesmentioning
confidence: 98%
“…FTICR operational parameters were optimized to maximize the abundance of the [A:CD+2H] 2+ peak, which was then subject to SWIFT isolation and to the subsequent ECD MS. The generation of noncovalent complexes [M:CD+2H] 2+ has previously been well documented in the literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The formation of noncovalent complexes, not covalent ones, was confirmed by performing sustained off-resonance irradiation collisionally activated dissociation (SORI-CAD) on the complex, which resulted in disassembly of the complex into its constituent ␤-CD and peptide (data not shown here) [48].…”
Section: Experimental/materials and Methodsmentioning
confidence: 52%
“…Many investigators have reported, on the basis of favorable 1:1 complex formation with aromatic group-containing compounds, that CD-guest noncovalent complexes formed in the gas phase were inclusion complexes that reflected the interactions in solution [14][15][16][17][18][19][20]. In contrast, Cunniff and Vouros reported that CD mixtures with amino acids or small peptides that might be least likely to form hydrophobic inclusion complexes in solution generally showed the most intense complex ions in their ESI-MS experiments [13]. Based on this finding, they suggested that the CD complexes were likely to be electrostatic adducts formed during the ESI process.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…8,9 Inclusion complex formation and chiral separation of amino acids and amino acid derivatives by CDs have been studied with different experimental techniques such as electrospray mass spectrometry, capillary electrophoresis and gas chromatography. [10][11][12][13][14] They have also been theoretically studied by molecular mechanics 15 and dynamics. 13,16,17 In these theoretical studies the presence of organic modifiers is represented by different values of the dielectric constant in the electrostatic contribution to the interaction energy.…”
Section: Introductionmentioning
confidence: 99%